Hubungan Kejadian Sibling Rivalry dengan Perkembangan Anak Pra Sekolah Di TK Ratu Alam Atakkae Kabupaten Wajo - Nirmawati Darwis; Fatmawati Fatmawai; Ruslang Ruslang; Ikdafila Ikdafila; Arni AR (Journal Research of Nursing & Midwifery (JRNM), 2025)
Sibling rivalry or competition between siblings arises when a child feels that parental attention is starting to decrease, the child experiences feelings of envy and dislike for the existence of his siblings. This kind of rivalry usually starts from the birth of the firstborn and can continue until they are adults and has the potential for long-term negative impacts. The purpose of this study was to determine the relationship between sibling rivalry and child development. This type of research is quantitative research using probability random sampling approach. This research was conducted in the Atakkae urban village area, Tempe District, Wajo Regency. Sampling consists of all parents who have children aged 3-6 years and have younger siblings with an age difference of under 3 years. The research instrument used a questionnaire sheet with data processing editing, coding, scoring, tabulating and analysis using the Chi-Square test and to assess frequency statistical data using a computer program, SPSS 2022. The results showed that most of the respondents, namely 19 people (55.9%), most children did not experience sibling rivalry. Most of the respondents, namely 17 people (50.0%), the development of pre-school children is doubtful. Based on the Chi-Square test, the significant value (p) = 0.000 α < 0.05, so Hi is accepted. The conclusion of this study is that there is a relationship between the incidence of sibling rivalry and the development of pre-school children at Ratu Alam Atakkae Kindergarten.